Intelligent Computer Mathematics 9th International Conference, CICM 2016, Bialystok, Poland, July 25-29, 2016, Proceedings - Kohlhase, Michael; Johansson, Moa; Miller, Bruce; de Moura, Leonardo; Tompa, Frank (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the refereed proceedings of the 9th International Conference on Intelligent Computer Mathematics, CICM 2016, held in Bialystok, Poland, in July 2016. The 10 full papers and 2 short papers presented were carefully reviewed and selected from a total of 41 submissions. The papers are organized in topical sections according to the five tracks of the conference: Calculemus; Digital Mathematics Libraries; Mathematical Knowledge Management; Surveys and Projects; and Systems and Data.